1987
DOI: 10.1128/jb.169.11.4923-4928.1987
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the lipopolysaccharide from a Rhizobium phaseoli mutant that is defective in infection thread development

Abstract: The lipopolysaccharide (LPS) from a Rhizobium phaseoli mutant, CE109, was isolated and compared with that of its wild-type parent, CE3. A previous report has shown that the mutant is defective in infection thread development, and sodium dodecyl sulfate-polyacrylamide gel electrophoresis shows that it has an altered LPS (K. D. Noel, K. A. VandenBosch, and B. Kulpaca, J. Bacteriol. 168:1392-1462. Mild acid hydrolysis of the CE3 LPS released a polysaccharide and an oligosaccharide, PS1 and PS2, respectively. Mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 32 publications
4
126
0
Order By: Relevance
“…Bacterial Strains-R. etli CE3 (the parent strain) and the R. etli mutants CE358 and CE359 were grown in a tryptone/yeast extract supplemented with Ca 2ϩ as described previously (25). Bacteria were harvested by centrifugation at late log/early stationary phase.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bacterial Strains-R. etli CE3 (the parent strain) and the R. etli mutants CE358 and CE359 were grown in a tryptone/yeast extract supplemented with Ca 2ϩ as described previously (25). Bacteria were harvested by centrifugation at late log/early stationary phase.…”
Section: Methodsmentioning
confidence: 99%
“…Polyacrylamide gel electrophoresis (PAGE) in the presence of deoxycholate (DOC) (27,28) of the water and phenol fractions indicated that LPS was recovered predominantly in the water layer in the case of strain CE3, while the two mutant strains yielded LPS in both the phenol and water layers. Water and phenol layers containing LPS were dialyzed and treated sequentially with ribonuclease, deoxyribonuclease, and proteinase K and then dialyzed and subjected to further purification by either gel filtration chromatography on Sepharose 4B (25,29) or by affinity chromatography on columns of polymyxin-agarose (Detoxi-Gel, Pierce). For the latter procedure, the crude extracts were treated with enzymes as described above and then dialyzed against 50 mM NH 4 HCO 3 , pH 8.0.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations